2002
DOI: 10.1088/0953-2048/15/6/323
|View full text |Cite
|
Sign up to set email alerts
|

(Cu,Tl)Ba2Ca3Cu4Ox compositions: I. The influence of synthesis time and temperature on the phase formation and evaporation$ndash$condensation mechanism

Abstract: Temperature and time dependence of the phase formation in the (Cu0.5,Tl0.5)-1234 composition have been studied. The liquid–vapour deposition mechanism for the formation of 12(n − 1)n superconducting phases is presented. XRD, SEM, EDS and weight loss data are discussed. Samples were superconducting with maximum Tc and Jc (at 60 K and 0.5 T), determined from M(H) loops of 118 K and 4 × 105 A cm−2, respectively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 37 publications
1
9
0
Order By: Relevance
“…For our experiments in a closed system (sealed Au tubes) a relatively good measure of the pressure inside the capsule is the weight loss and weight loss rate. Our data have shown that weight loss increases with time for any given temperature following a sigmoid-type curve [1]. Increase in synthesis temperature for the same synthesis time leads to an increase in weight loss.…”
Section: Introductionmentioning
confidence: 50%
See 4 more Smart Citations
“…For our experiments in a closed system (sealed Au tubes) a relatively good measure of the pressure inside the capsule is the weight loss and weight loss rate. Our data have shown that weight loss increases with time for any given temperature following a sigmoid-type curve [1]. Increase in synthesis temperature for the same synthesis time leads to an increase in weight loss.…”
Section: Introductionmentioning
confidence: 50%
“…Special attention is paid to Cpurification of the oxides. Details are presented in [1]. In fact, for the synthesis of the samples discussed here we have used heat-treated oxides from the same batches as in [1].…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations